S73 Circulating Regulators of Acute Muscle Wasting in the Critically Ill: GDF-15 a Potential Novel Driver of Acute Muscle Wasting. (19th November 2012) - Bloch, SAA; Lee, JY; Wort, SJ; Polkey, MI; Kemp, PR; Griffiths, MJD
Abstract : Introduction: Acute muscle wasting in the critically ill manifesting as intensive care unit acquired paresis (ICUAP) is common, and causes significant morbidity and mortality. The pathological mechanisms underlying ICUAP are poorly understood and, other than rehabilitation, no therapeutic interventions exist. It was hypothesised that known or potential circulating modulators of muscle mass: insulin-like growth factor-1 (IGF-1), myostatin and growth and differentiation factor-15 (GDF-15) would have distinct dynamic profiles in patients who develop acute muscle wasting in a novel human model of ICUAP. Methods: In a prospective observational study of 42 patients undergoing elective high-risk cardiothoracic surgery (at the Royal Brompton Hospital, London, UK) those who developed muscle wasting were identified by ultrasound. Circulating IGF-1, myostatin and GDF-15 were assayed pre-operatively and over the first week post-operatively. The ability of GDF-15 to cause muscle wasting in vitro was determined in cultured C2C12 myotubes. Main results: 23 of 42 patients (55%) developed quadriceps atrophy. Plasma concentrations of IGF-1 and unexpectedly myostatin, known mediators of muscle hypertrophy and atrophy respectively, both decreased from baseline in the first post operative days. By contrast, plasma GDF-15 concentrations increased in all patients. This increase in GDF-15 was higher (535%±308% versus 495%±247%) and sustained at day 7 in those who developed muscle wasting (day 7 compared with baseline, p<0.01), but recovered in the non-wasting group (p>0.05). Furthermore IGF-1 also did not recover in those who developed muscle wasting (day 7 compared with baseline, p<0.01) but did in the non-wasting group (p>0.05). Myostatin recovered to baseline in both groups. Finally, we demonstrated that GDF-15 caused atrophy of myotubes in vitro (average control myotube diameter was 26.3±9.0 µm versus 22.3±7.5 µm for GDF-15 treated myotubes, equating to 15% myotube atrophy, p= 0.011). Conclusion: This data supports the hypothesis that acute muscle loss occurs as a result of an imbalance between drivers of muscle atrophy and hypertrophy. GDF-15 is a potential novel mediator of muscle atrophy in ICUAP, which may become a therapeutic target in patients with ICUAP and other forms of acute muscle wasting.